Using Conservative Condylectomy for Management of a Large Osteochondroma of the Mandibular Condyle With 6-Year Follow- up - Santos, George Soares; Gomes, Julio Bisinotto; Maia, Sergio de Sousa; Bermejo, Patricia Rota [UNESP]; Shinohara, Elio Hitoshi [UNESP]; Sonoda, Celso Koogi [UNESP]; Melo, Willian Morais de [UNESP] (Lippincott Williams & Wilkins, 2014)
Osteochondroma is a hamartomatous proliferation of cartilaginous tissue, which is the most common benign tumor of the long bones, but is relatively rare in the maxillofacial region. Most cases of mandibular condylar osteochondroma manifest with facial asymmetry or malocclusion with limited temporomandibular joint movements. Several approaches for management of this lesion have been proposed, as conservative condylectomy technique. This procedure has been suggested a valid approach to minimize facial asymmetry, contributing to the recovery of occlusion associated with no local tumor recurrence, and without condylar reconstruction procedure. Therefore, this article aims to describe a clinical report of a true osteochondroma of the mandibular condyle in a 35-year-old patient who was successfully treated using conservative condylectomy procedure.
Keywords: Bone tumor; craniomandibular disorders; facial asymmetry; osteochondroma; mandibular condyle; surgical management